The Role of CSR Engagement in Customer-Company Identification and Behavioral Intention During the COVID-19 Pandemic - Wu, Yanqin; Zhu, Wenzhong (Frontiers in Psychology, 2021)
The global coronavirus pandemic has aroused a strategic discussion among business about CSR engagement when the strong vitality of online social media has caused dramatic changes on social interaction. In view of the global economic downtown introduced by the COVID-19 pandemic, the presented research is devoted to investigating whether CSR engagement in social media can help Chinese shared brands at stake survive from the overwhelming crisis. A theoretical model proposed to describe the hypothesized relationships was tested by a Structural Equation Modeling technique through the empirical online questionnaire. Through findings, we demonstrated that there is a positive relationship between CSR engagement of DiDi (a Chinese car-sharing platform) on WeChat, customer-company identification and customers’ behavioral intention. On consideration of psychological influence, it was found that the effect of CSR engagement on customers’ behavioral intention was mediated by customer-company identification. In view of implications, the present research highlights the significant role of CSR engagement in a critical period theoretically and offers business more open innovation strategies to compete against the COVID-19 pandemic-induced market downturn.